2010
DOI: 10.1039/c0dt00005a
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium complexes bearing functionalized trisamido ligands and their reactivity in the polymerization of ε-caprolactone and rac-lactide

Abstract: The addition of 1 and 2 equivalents of AlMe(3) to cis,cis-C(6)H(9)(NHCH(2)C(6)H(4)-o-R)(3) (R = PPh(2) (3) and SPh (4)) gives complexes [cis,cis-C(6)H(9)(NCH(2)C(6)H(4)-o-R-kappaN)(2)(NHCH(2)C(6)H(4)-o-R-kappaN)]AlMe (R = PPh(2) (7) and SPh (8)) and [cis,cis-C(6)H(9)(NCH(2)C(6)H(4)-o-R)(3)-kappa(5)mu(2)N]Al(2)Me(3) (R = PPh(2) (5) and SPh (6)), respectively. The bimetallic complexes are active in the polymerization of epsilon-caprolactone and rac-lactide whereas the monometallic complexes are not, although no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…A similar trend was also observed by Thibault and Fontaine. 40 Kinetic studies of ε-caprolactone polymerization e The M n value was calculated according to M n = 0.56M n GPC , where M n GPC was determined by GPC (chloroform), and is relative to polystyrene standards. first-order dependence of reaction rate on monomer concentration.…”
Section: Ring-opening Polymerization Of ε-Caprolactonementioning
confidence: 99%
“…A similar trend was also observed by Thibault and Fontaine. 40 Kinetic studies of ε-caprolactone polymerization e The M n value was calculated according to M n = 0.56M n GPC , where M n GPC was determined by GPC (chloroform), and is relative to polystyrene standards. first-order dependence of reaction rate on monomer concentration.…”
Section: Ring-opening Polymerization Of ε-Caprolactonementioning
confidence: 99%
“…Mu and coworker reported that, in the absence of alcohol, dinuclear aluminum dimethyl complexes supported by aldimine‐anilido ligands were inactive toward the polymerization of cyclic esters. Thibault and Fontaine found that, without the addition of alcohol, the ROP of ε ‐CL catalyzed by aluminum methyl complexes with phosphine/thiol‐amido ligands was badly controlled and no clear initiation mechanism could be drawn. The aluminum complexes reported in this work are rare examples that could initiate the ROP of cyclic esters with living features in addition to our previous report …”
Section: Resultsmentioning
confidence: 99%
“…A key step to obtain well defined materials with beneficial mechanical properties is rigid control of the polymer chain microstructure. Although there are reports on highly active and very selective dinuclear organoaluminium catalysts for ring opening polymerisations (ROP) of cyclic esters, structural studies and analyses concerning potential cooperative effects remain relativly scarce 56–58. On the other hand, in the last twenty years numerous examples of β ‐diketiminato aluminium complexes have been published, [1,43,44,47–54] including a homoleptic tris‐ β ‐ diketiminato aluminium complex,55 an aluminium(I) complex52 and a complex containing an Al–O–Al moiety, claimed to be the smallest MAO model conceivable 54.…”
Section: Resultsmentioning
confidence: 99%